Essays in Monetary Economics - Rudel, Paul; Justus Liebig University Giessen (My University, 2024)
The papers included in this dissertation were composed during a period of considera-ble turmoil in many respects. But, it is always darkest before the dawn. Thus, for academic research, such periods open new venues and enable a reassessment of existing findings. The event that has by far the greatest influence on the essays submitted here is the Global Financial Crisis. In particular, the crucial role of credit, the use and effective-ness of prudential measures in order to regulate credit developments, as well as the domestic and foreign (side-)effects of U.S. unconventional monetary policy, which the Fed employed with particular intensity in order to address the severe economic challenges posed by the financial crisis. In response to the global economic downturn, central banks across the globe have taken swift and decisive action to lower their key interest rates. However, once the zero lower bound was reached, this sword became blunt, necessitating the implementation of unconventional measures. This strategy proved effective, resulting in a dis-cernible economic recovery, i.a. by reviving labor markets. Concurrently, the central banks’ asset-purchasing programs precipitated a notable surge in stock markets and asset prices. In turn, it is perceived that only a relatively limited proportion of the popu-lation has benefited from this appreciation, giving rise to heightened discourse sur-rounding the nexus between income inequality and the impact of (ultra-loose) mone-tary policy. In the first paper, Moving closer or drifting apart: Distributional effects of monetary policy, which is joint work with Lucas Hafemann and Jörg Schmidt, we examine said nexus between unconventional monetary policy and inequality in six advanced econ-omies. Furthermore, we analyse the two major transmission channels at work. The examined countries vary in their extent of governmental redistribution, allowing for an evaluation of whether governmental interventions affect the impact of unconventional monetary policy on income equality. To this end, we incorporate Gini coefficients in an otherwise standard vector autoregressive macro model, where we identify monetary policy shocks by means of sign restrictions. Our findings show that, on the one hand, expansionary monetary policy shocks are associated with an increase in the Gini coefficients of gross incomes across all coun-tries. On the other hand, only countries with relatively limited redistribution show a significant response of net income inequality as well. In order to gain a deeper understanding of the underlying mechanism at play, we ex-amine the two most relevant transmission channels: the employment channel and the income composition channel. We find that employment, captured by the total number of employed people, increases due to loose monetary policy in all countries. Once more, the reaction is observed to be weaker and less pronounced in countries with a high degree of redistribution (i.e. with a presumably more active state with potentially stricter regulations and, in turn, less flexible labor markets). In order to examine the income composition channel, we disaggregate the composition of net national income into its two major parts, labor-related income and capital-related income. This allows for an evaluation of the extent to which each category benefits disproportionately. Our results show that while both components are, in general, affected in a positive man-ner, the ratio of these components indicates that in the U.S., Canada, and South Korea, those who own capital benefit disproportionately. As the rise in employment is insufficient to offset the surge in net income inequality, it can be concluded that the composition of income has a greater impact than the positive effects of the labor mar-ket. Lastly, the capital-to-wage ratio indicates that in countries with a considerable degree of redistribution, both income sources appear to be affected in a similar manner. In summary, this paper contributes two findings to the existing literature. Firstly, the disproportional surge in capital income is the driving force behind the increase in net income inequality and secondly, redistribution is capable of mitigating the effects of unconventional monetary policy on income dispersion. In a globally interconnected world, the unintended and intended consequences of (un-conventional) monetary policy extend beyond the confines of national borders. The existing literature clearly shows that the Federal Reserve’s conventional monetary policy measures extend beyond the United States to both advanced and developing countries. Following the Global Financial Crisis, the Fed’s policy was constrained by the zero lower bound on interest rates, such that she was forced to employ unconven-tional measures. One such measure is forward guidance, which is utilized to manage expectations regarding future Fed policies. Nevertheless, while the spillover effects of conventional monetary policy measures have been extensively researched, there is a lack of literature concerning the spillover effects of unconventional monetary policy. The second submitted essay aims at filling this gap. News shocks spillovers: How the euro area responds to expected Fed policy, which is a joint effort with Peter Tillmann, is devoted to examining the cross-border effects of U.S. unconventional monetary policy on expectations and sentiment in the euro area. To this end, we identify monetary news shocks, i.e. new information about the Fed’s future monetary policy becoming available today, based on a vector auto-regression (VAR) pproach and estimate the responses of euro area variables to an anticipated Fed tightening. We find that a U.S. news shock improves sentiment and business cycle expectations in the euro area. More precisely, asset prices, expectations about future economic activity, and sentiment indicators in the euro area appreciate in light of an anticipated Fed policy tightening. The findings are in line with the notion that an announcement issued today about a future tightening reveals private information the Fed might have about the state of the U.S. economy. This favorable news trigger an upward revision of sentiment indicators in the euro area. We underline this interpretation by showing that the news shocks, although raising expected future interest rates, also raise equity prices in the U.S. and, at the same time, lower equity market volatility. Hence, it is the new information about a stronger than expected economic expansion that spills over to the euro area. A crucial driving factor for the Global Financial Crisis were the credit developments in the preceding years. The empirical literature demonstrates that boom-bust phases observed in the past four decades go back to credit supply expansions. Furthermore, unhinged credit developments can lead to vicious boom-bust cycles. That is, the initial stimulation of economic activity subsequently results in financial and banking crises, culminating in severe recessions. Notwithstanding their dominant role in economic activity in the short and medium term, the existing literature has been largely confined to examining the effects of disturbances in credit supply in a linear world. In my third essay, Do credit supply shocks have asymmetric effects?, which is joint work with David Finck, we tackle this short-coming by assessing whether positive and negative credit supply shocks cause analogous patterns in the U.S. economy. This endeavor is relevant for two reasons. First, the theoretical literature on the responses to financial distortions is extensive and hints at potential asymmetries (and nonlinearities). Second, if potential asymmetries are disregarded, the true effects will be underestimated, as originally differently operating shocks eventually level out in a symmetric setup. We test whether and to what extent asymmetries are present by identifying credit supply shocks via sign restrictions in a structural VAR and separating them into positive and negative. Using local projections, we find that positive credit supply shocks leave notably different patterns in private debt, mortgage debt, and debt:GDP, as op-posed to negative credit supply shocks. However, even though this paper does not aim at tracing down the specific causes of asymmetries, we find that house prices, and thus the household-driven demand channel, are key for the persistence in the responses of mortgage debt and debt:GDP to credit supply shocks. Furthermore, our results underpin the narrative of the boom-bust cycle in the presence of financial distortions which, again, is more pronounced in the presence of posi-tive credit supply shocks. For example, after an initial increase in economic activity, that lasts for five to ten quarters, the economy transits into a bust phase with a nota-ble slowdown in economic activity. In contrast, negative credit supply shocks cause notably stronger deflationary pressure. The concluding paper of this doctoral thesis also addresses the impact of credit sup-ply shocks. However, it concentrates specifically on the role of prudential regulation. This has become an invaluable tool for steering credit growth and thus, enhancing the stability of financial systems. Accordingly, this toolbox is being used more and more frequently. However, in order to assess the use and effectiveness of prudential measures, the existing literature focuses on the direct effects of systematic or unsystematic prudential policies on economic outcomes such as credit growth or economic activity. In Loan supply shocks, prudential regulation, and the business cycle, I adopt a novel approach to examining the role of prudential regulation and analyze the extent to which the regulatory environment itself shapes the business cycle effects of loan supply shocks. To this end, first, I derive regulatory cycles from a cumulative prudential policy index that tracks the evolution of the regulatory stance in the euro area. Using sign re-strictions in a state-dependent local projections framework, I then identify loan supply shocks and analyse their business cycle effects conditional on whether the regulatory regime is tight or loose. The results suggest that in tight regimes, expansionary shocks trigger a noticeable boom-bust cycle. That is, key economic variables turn into a bust phase after an initial expansion, which lasts for about four quarters. These re-sults hold regardless of the frequency of the chosen regulatory cycle. In the loose re-gime, results appear inconclusive due to the sensitivity of the outcomes to the under-lying regulatory cycle frequency. Moreover, a comparison of the business cycles effects revels asymmetric responses to loan supply shocks across regimes. Especially loan growth, which is of particular interest for prudential regulation, shows notably differing results. In the tight regime, expansionary loan supply shocks do not sustainably increase credit growth. In con-trast, in the loose regime, lending follows a sustained growth path as a result of the shock. As noted, the responses found in a loose regulatory regime are not as robust. A key reason for this is that it is difficult to clearly identify loose regimes, as prudential measures have so far mainly taken only one form: tighter. However, even if this paper cannot provide a definite conclusion, the tendencies for asymmetric effects should not be completely ignored in light of the importance of credit development for prudential regulation.
Keywords: Unconventional monetary policy; Income indequality; Expected monetary policy; Expectations; Euro area; Credit supply shocks; Indebtedness; Prudential regulation; State-dependency; Local projections; ddc:330